(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: (1) To describe the compliance with swallowing rehabilitation exercises among head and neck cancer patients undergoing radiotherapy at Nghe An Oncology Hospital, and (2) To analyze factors associated with adherence levels in this population. Methods: An analytical cross-sectional study was conducted on 103 head and neck cancer patients indicated for definitive or adjuvant radiotherapy from January 2025 to September 2025. Adherence to seven swallowing rehabilitation exercises was evaluated via face-to-face interviews on the final day of the radiotherapy course. Data were processed using SPSS 26.0, and logistic regression analysis was performed to identify associated factors (p<0.05). Results: The overall compliance rate with swallowing exercises was 61.2%. Adherence was highest for postural adjustment exercises (64.1%) and lowest for the Masako maneuver (32.0%) and the Mendelsohn maneuver (48.5%). Statistically significant predictors of higher compliance (p<0.05) included high school education or above (OR=3.63), non-smoking status (OR=3.00), non-alcohol consumption (OR=2.83), absence of psychological distress (OR=2.54), and early disease stage I–II (OR=6.78). Conversely, radiation-induced toxicities (pain, oral mucositis, nausea) and practical barriers (perceived inconvenience, difficulty remembering exercises, high frequency/difficulty, lack of caregiver support) significantly reduced compliance (p<0.05). Notably, patients experiencing dysphagia symptoms were 2.61 times more likely to adhere than those without dysphagia (p<0.05). Conclusions: Compliance with swallowing rehabilitation exercises among head and neck cancer patients receiving radiotherapy remains moderate. Effective management of radiation toxicities, simplification of exercise protocols, and enhanced support from healthcare providers and family members are pivotal strategies to improve treatment adherence.